2019
DOI: 10.1108/ijhcqa-07-2018-0190
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of education, in-service training and tenure prolongation as methods for enhancing nursing performance

Abstract: Purpose The purpose of this paper is to provide an empirical basis for considering in-service training, tenure prolongation and continuing education as methods for enhancing nursing performance. Design/methodology/approach A self-reported questionnaire was used to collect data from 532 nurses, who were selected using the simple random sampling method from ten hospitals in Accra North, Ghana. Confirmatory factor analysis (CFA) was used to test the study’s hypotheses. Findings The resulting model is of good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
(104 reference statements)
3
9
0
3
Order By: Relevance
“…In the present study, it was found that educational level increased job performance levels of nurses, and those holding an undergraduate or postgraduate degree had higher levels than those holding a high school diploma or associate's degree. Similar to our results, some studies have found that high levels of education improve nurses' skills such as critical decision-making, planning, and performing daily routine tasks, thereby increasing job performance levels (Asiamah et al, 2019;Okab, 2017;Tong, 2018). Contrary to these findings, Soilkki et al (2014) and Mohammad Ahmed and Ahmed (2019) found that nurses did not prefer to get a postgraduate degree since high education levels did not promote a sustainable compensation system within the organisations (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, it was found that educational level increased job performance levels of nurses, and those holding an undergraduate or postgraduate degree had higher levels than those holding a high school diploma or associate's degree. Similar to our results, some studies have found that high levels of education improve nurses' skills such as critical decision-making, planning, and performing daily routine tasks, thereby increasing job performance levels (Asiamah et al, 2019;Okab, 2017;Tong, 2018). Contrary to these findings, Soilkki et al (2014) and Mohammad Ahmed and Ahmed (2019) found that nurses did not prefer to get a postgraduate degree since high education levels did not promote a sustainable compensation system within the organisations (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, prior research has found that training and development participants demonstrate more innovative behaviors than nonparticipants (Susomrith et al , 2019). In the nursing context, formal education and training as well as tenure prolongation are responsible for enhancing nurses' performance (Asiamah et al , 2019). While Araujo and Figueiredo (2019) recommended that polite attitudes and behaviors among nursing staff members would ensure the promotion of a pleasant working environment, a slightly more recent study proposed that the confidence and capacity of professionals to address cancer survivorship problems could be solved through education and proper training (Drurya et al , 2020).…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…Consequently, scholars have highlighted various predictors when exploring employee performance, such as motivation, achievement and transfer; motivation to learn; conscientiousness; anxiety, self-efficacy; innovation behavior; confidence and capacity; tenure prolongation, etc. (Noe, 1986; Velada and Caetano, 2007; Asiamah et al , 2019; Susomrith et al , 2019; Drurya et al , 2020).…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…Asiamah y col. (9) encontraron que la realización de programas de orientación clínica y sesiones de formación periódicas para apoyar el desarrollo de la carrera de las enfermeras aumentaba sus niveles de rendimiento laboral; en línea con los resultados de nuestro estudio, se sustenta la necesidad de una formación continua como forma de garantizar la calidad de los cuidados de enfermería. Sharma y col. (10) plantean que las enfermeras que trabajan en instituciones que invierten en su desarrollo y educación y dan importancia al empoderamiento de las enfermeras tenían mayores niveles de compromiso emocional y rendimiento laboral.…”
Section: Discussionunclassified